2016
DOI: 10.1007/s10120-016-0674-5
|View full text |Cite
|
Sign up to set email alerts
|

Side overlap esophagogastrostomy to prevent reflux after proximal gastrectomy

Abstract: SOFY can be easily performed laparoscopically and may overcome the problems of postoperative reflux and stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 10 publications
0
78
0
Order By: Relevance
“…Excessive overlapping of the valve is likely to cause ischaemic necrosis of the valve or anastomotic stenosis. Yoshito Yamashita [22] et al reported an anastomotic anti-reflux method of oesophageal-remnant stomach side overlap via a linear cutter stapler under complete laparoscopy. We believe that in this method, a long segment of the lower oesophagus needs to be reserved, which cannot guarantee upper margin R0 resection of Siewert II AEG tumours with dentate line invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive overlapping of the valve is likely to cause ischaemic necrosis of the valve or anastomotic stenosis. Yoshito Yamashita [22] et al reported an anastomotic anti-reflux method of oesophageal-remnant stomach side overlap via a linear cutter stapler under complete laparoscopy. We believe that in this method, a long segment of the lower oesophagus needs to be reserved, which cannot guarantee upper margin R0 resection of Siewert II AEG tumours with dentate line invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, Yamashita et al [32] proposed a side overlap esophagogastrostomy to prevent reflux after PG, with excellent results in patients undergoing this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Reflux esophagitis is a major concern after PG. In several studies addressing this concern, it has been reported that direct anastomosis between the esophagus and the remaining stomach may lead to significant gastroesophageal reflux, esophagitis, and stricture at varying degrees (18,19). Reflux symptoms after PG are one of the leading causes of pain and impaired quality of life after surgery in patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%